France : Financial Sector Assessment Program-Technical Note-Nonfinancial Corporations and Households Vulnerabilities. (IMF Staff Country Reports; Country Report ;, 2019)
This technical note on nonfinancial corporations and households vulnerabilities on France analyzes the structure of nonfinancial corporate financing in the French economy, potential vulnerabilities of the corporate sector, and their possible channels of transmission through interconnections with the financial system. The objective of this paper is to document the evolution of French corporate debt since the global financial crisis, analyze the riskiness of this debt, the quality of allocation of this debt, and uncover potential heterogeneity across sectors and firms which may have implications at the macroeconomic level. This paper also complements existing studies by the Institut National de la Statistique et des Etudes Economiques, the Haut Conseil de Stabilite Financiere and the Banque de France by undertaking a cross-country comparative analysis. Empirical analysis suggests that corporate debt may be allocated efficiently across publicly listed companies, but the picture is less clear among nonpublicly listed firms.